Specification for welding electrodes and rods for cast iron (American Welding Society, 2016)
The chemical composition requirements for electrodes and rods for welding cast iron are specifed. Copper-base rods used for braze welding of cast iron are not included. Major topics include general requirements, testing, packaging, and application guidelines.
"AWS A5.15:1990 (R2016), an American National Standard."
"Supersedes AWS A5.15-90 (2006)."
"Approved by American National Standards Institute, May 5, 2016."
Keywords: Electric welding -- Electrodes -- Specifications -- United States.; Welding rods -- Specifications -- United States.; Cast-iron -- Welding.; elektronické knihy; electronic books